Monocular Diplopia and Nondisplaced Inferior Rectus Muscle on Computed Tomography in a Pediatric Pure Orbital-Floor Fracture. Issue 7 (October 2018) - Joganathan, Varajini; Gupta, Deepak; Beigi, Bijan
Abstract : Abstract: Trapdoor fractures are common in children because of elastic nature of the pediatric bone. Clinical signs and radiological evidence in these cases may be minimal. This study involves a 14-year-old girl who sustained blunt trauma to her left eye. Initial investigation, for pure orbital floor fracture included computerized tomography (CT scan) of the orbit, did not show any evidence of incarcerated rectus muscle. She had no limitation of extraocular movements nor enophthalmos. Following conservative treatment, she had a left persistent orbital pain and left monocular diplopia. This prompted a magnetic resonance imaging (MRI) of the orbit investigating soft tissue, which found fine partial muscle herniation through the self-sealed fracture needing surgical intervention. Although an orbital CT imaging is preferrd, in this acute setting, magnetic resonance imaging should be considered to delineate the soft tissue anatomy in relation to a trapdoor fracture, especially when there are not cardinal associated physical symptoms with a trap door fracture such as restricted eye movement and enophthalmos. Mono-ocular diplopia can be noted as an associated symptom to prompt early surgical repair.